Uji Aktivitas Antibakteri Lendir Bekicot (Achatina Fulica) Terhadap Bakteri Escherichia Coli Dan Uji Kadar Total Protein - Otu, Larasati Rambu; Iswandi, Iswandi; Wulandari, Destik (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2024)
Snails (Achatina fulica) have mucus whose main contents include beta agglutinin, Achasin protein, oacharan sulfate and glycoconjugates. Snail mucus can also treat wound infections in the digestive tract and surgical site infections (SSI), one of which is caused by Escherichia coli bacteria. This research utilizes the antibacterial content in snail mucus to inhibit Escherichia coli bacterial colonies and determine the total protein levels in snail mucus. The antibacterial activity test used the disk diffusion method and analysis of total protein levels in snail mucus was analyzed using the biuret method with a UV-Vis spectrophotometer and albumin as a standard solution. The research results were entered in tabular data and analyzed descriptively. The results of quantitative tests on the antibacterial activity of snail mucus showed that there was antibacterial activity of snail mucus against Gram negative Escherichia coli bacteria with concentrations of 100%, 50% and 25% having clear zones of 14, 11.88 and 8.66 mm respectively. The results of calculating the total protein content using the UV-Vis Spectrophotometer method were 11%. This test produced a high total protein content